Lean Service Operations and A Lean Management Application at a Foundation University - Mira, Almohanad; Kuşakcı, Ali Osman (Universitas Islam Indonesia, 2022)
Lean service operations and lean management are of vital importance for all service providers as much as manufacturers. Unfortunately, most universities need to be made aware of the concept of lean. However, they can benefit from lean management in all their service areas, such as admissions, administration of research funds, hiring, and nearly any functional area where multi-step processes can be simplified and focused on the needs of the users served by the organization. Lean methodologies focus on reducing waste (Muda in Japanese), removing overburden (Muri in Japanese), and unnecessary variation (Mura in Japanese). Non-value-added activities are eliminated or dealt with to develop the performance of the process. This study aims to highlight the suitability of lean in a university environment to enhance the efficiency of the operational tasks performed and provide suggestions for better performance. Lean methodologies were applied to the School of Graduate Studies at a Turkish university to study the current state of the process and provide recommendations and alternatives for the current issues faced using Value Stream Mapping (VSM). As a result, Value-Added and Non-Value-Added activities were identified with Indicative Ratios to compare the performance before and after applying lean. In the end, seven questions were answered to develop a proposal for the future state of the process, which was presented to the university management.